ASSESSING THE EFFECT OF THERMAL TREATMENT ON MEAT PROTEINS USING PROTEOMIC METHODS - Irina M. Chernukha; Anastasiya G. Akhremko (Теория и практика переработки мяса)
The results of studying the effect of various temperatures on the protein composition of minced meat from porcine m. longissimus dorsi by two-dimensional electrophoresis are presented. The most complete distribution of protein fractions was observed in fresh raw minced meat, and when it was exposed to negative temperature, there was a sharp decrease in protein components (carbonic anhydrase 3, αβ-crystallin), as well as a decrease in the staining intensity of protein spots of the main constitutive fractions (tropomyosin alpha 1, myosin light chain 1). In the case of heat treatment, structural muscle proteins were retained with some changes in high molecular weight fractions, namely, protein molecules degraded to compounds with a simpler structure. It was noted that fractions of tropomyosin β-chain, triosephosphate isomerase 1, myosin light chains 2 were not detected after minced meat was frozen, while tropomyosin alpha 1 was retained in all samples.